MEWUJUDKAN PESERTA DIDIK TERAMPIL DAN MANDIRI MELALUI KEWIRAUSAHAAN DI SEKOLAH SATU ATAP - SITI NURCHAYATI (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2022)
One-Stop School is a government innovation in compulsory education programs in Remote, Scattered, and Isolated (3T) areas. Realizing skilled and independent students is the vision of SMPN Satu Atap Tambelang. The condition of SMPN Satu Atap Tambelang is still limited in infrastructure, school operational costs are minimal, input from students with learning motivation is still lacking, and the economic status of the majority of the economy is substandard. The entrepreneurship program is a choice of solution that matches the characteristics of SMPN Satu Atap Tambelang. This program , which is indeed the competence of the principal, is carried out through the development of insights (theory) to actualization (practice) in the field. The entrepreneurship program is a process to get a creative, innovative, unyielding, responsible, disciplined, and other entrepreneurial spirit . During the program implementation process, students, totaling 64 people, were observed using instrument sheets that measured skilled and independent attitudes. Dobtained data that after the implementation of the program the number of students who were skilled enough to be highly skilled became 98% or as many as 63 children, with an increase of 86%. Meanwhile, independence, obtained an increase of 95%, from only 3 people to as many as 64 people. The conclusion obtained is that by direct practice of business activities in schools, students can feel, study, and understand the concept of entrepreneurship so as to form the attitude and entrepreneurial mentality of students, namely skilled and independent. ABSTRAKSekolah Satu Atap merupakan inovasi pemerintah dalam program wajib belajar pada daerah Terpencil, Terpencar, dan Terisolir (3T). Mewujudkan peserta didik yang terampil dan mandiri menjadi visi SMPN Satu Atap Tambelang. Kondisi SMPN Satu Atap Tambelang masih terbatas sarana prasarana, biaya operasional sekolah minim, input peserta didik dengan motivasi belajar masih kurang, serta status ekonomi mayoritas ekonomi di bawah standar. Program kewirausahaan menjadi pilihan solusi yang cocok dengan karakteristik SMPN Satu Atap Tambelang. Program ini yang memang menjadi kompetensi kepala sekolah dilakukan melalui kegiatan pengembangan wawasan (teori) sampai dengan aktualisasi (praktik) di lapangan. Program kewirausahaan menjadi proses untuk mendapatkan karakter kreatif, inovatif, pantang menyerah, bertanggungjawab, disiplin, dan jiwa enterpreneur lainnya. Selama proses pelaksanaan program, peserta didik yang berjumlah keseluruhan 64 orang, diamati menggunakan lembar instrumen yang mengukur sikap terampil dan mandiri. Diperoleh data bahwa sesudah pelaksanaan program jumlah peserta didik yang cukup terampil hingga sangat terampil menjadi 98% atau sebanyak 63 anak, dengan peningkatan sebesar 86%. Sedangkan kemandirian, memperoleh peningkatan 95%, dari hanya 3 orang menjadi sebanyak 64 orang. Kesimpulan yang diperoleh adalah dengan praktik langsung kegiatan usaha di sekolah peserta didik dapat merasakan, menelaah, dan memahami konsep kewirausahaan sehingga membentuk sikap dan mental kewirausahaan peserta didik yaitu terampil dan mandiri..